"I always swim badly in the final" - Marshall, B. D. (Applied Swimming Programme Schedule - 27th International Conference on Biomechanics in Sports, 2009)
As coaches we have all experienced the situation where a swimmer starts making destructive or negative comments that impact their ability to perform to their maximum. Such destructive thinking is well known in psychology, for example, amongst clients who experience anxiety or are depressed. In swimmers, we hear them blaming others, feeling guilty, predicting (negative) results before they happen and exaggerating previous negative results. Furthermore, swimmers can experience a mental block in terms of how to overcome an obstacle which, in their minds, seem impossible to overcome. In this talk I will introduce several practical tools and techniques that can be used by the coach to aid the swimmer in thinking in a constructive way. These tools and techniques have been developed in the fields of Cognitive Behavioural Therapy and within Life Coaching (sometimes referred to as Executive Coaching) and can be applied over a period of weeks or months, or at the competition site itself. By developing the practical tools that I introduce here, coaches should feel more empowered in dealing with these problems rather than feeling exasperated or annoyed at the negative thoughts of their swimmers.